Philosophy of Science as an Epistemological Foundation in the Development of Science - Muharleni; Yeni Karneli; Puji Gusri Handayani (Islamic Studies and Education Journal, 2025)
The philosophy of science plays a fundamental role as an epistemological foundation in the development of science. This article examines the role of the philosophy of science in shaping the rational and methodological basis of scientific thinking, as well as its implications for innovation and integration of contemporary science. The research method used is a reflective-analytical literature study by examining classical and contemporary literature related to the philosophy of science and epistemology. The results of the study indicate that the philosophy of science not only provides a conceptual framework for the validation and justification of knowledge, but also guides the selection of appropriate scientific methods and facilitates interdisciplinary dialogue. In addition, the philosophy of science plays a crucial role in emphasizing the ethical dimensions and social responsibility in the development of science, especially amidst the increasingly complex and pluralistic challenges of the modern and postmodern eras. Thus, strengthening the philosophy of science is key to encouraging the development of science that is not only innovative, but also holistic and sustainable.